DEKONSTRUKSI NARASI SEJARAH DAN IDENTITAS DALAM NOVEL AMBA KARYA LAKSMI PAMUNTJAK: ANALISIS POSTSTRUKTURALISME JACQUES DERRIDA - Fatinah Nur Waqiah; Andi Karman; Aslan Abidin (STKIP Subang, 2026)
This study aims to analyze the novel Amba by Laksmi Pamuntjak using the Poststructuralism paradigm through Jacques Derrida’s strategy of Deconstruction. Laksmi Pamuntjak’s Amba is analyzed based on the dismantling of binary oppositions, the process of deferred meaning (différance), and the presence of the trace (trace). The research method employed is the qualitative descriptive method. This study utilizes stages of deconstructive analysis, including reconstruction, deconstruction, and reinscription. The analysis process was conducted by collecting data findings in the form of words, phrases, clauses, sentences, and paragraphs within the research object that indicate the instability of meaning. This study found various forms of deconstruction of historical narratives and identities within Laksmi Pamuntjak’s novel Amba. The dismantling of binary oppositions was found in the hierarchical shift between History and Fiction, where the text challenges the dominance of official history through personal narratives. Furthermore, the concept of différance is illustrated in the identity of the character Amba, which is fluid and consistently defers the finality of meaning. Meanwhile, the presence of the trace (trace) explains the remnants of wayang myths present to demonstrate the limitations of language in encapsulating the historical trauma of 1965. This study concludes that the novel Amba actively deconstructs itself by rejecting the authority of a single meaning.